Iberian (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2020)
Iberian is the best documented of all Palaeohispanic languages —it has the richest and most varied corpus, the longest chronology of attestation and largest territorial extension—, and yet it also remains one of the most enigmatic. As for its typological classification, it is considered to be an agglutinative language which may present ergative features; however, its hypothetical relationship with other languages, ancient or modern, is still uncertain. This paper presents the main ongoing lines of research and the most widely accepted hypotheses on the Iberian language and its written culture, placing special emphasis on current problems of interpretation and the main challenges ahead.